Sm doped mesoporous CeO2 nanocrystals: aqueous solution-based surfactant assisted low temperature synthesis, characterization and their improved autocatalytic activity. Issue 4 (24th December 2015) - Mandal, Bappaditya; Mondal, Aparna; Ray, Sirsendu Sekhar; Kundu, Amar
Abstract : Mesoporous nanocrystalline high surface area CeO2 synthesized at 100 °C exhibited improved autocatalytic activities by modifying defect states and reducibility upon Sm 3+ doping. Abstract : Mesoporous Sm 3+ doped CeO2 (Ce–Sm) with a nanocrystalline framework, a high content of Ce 3+ and surface area (184 m 2 g −1 ), have been synthesized through a facile aqueous solution-based surfactant assisted route by using inorganic precursors and sodium dodecyl sulphate as a template. The XRD results indicate that the calcined Ce–Sm and even the as-prepared material have a cubic fluorite structure of CeO2 with no crystalline impurity phase. XRD studies along with HRTEM results confirmed the formation of mesoporous nanocrystalline CeO2 at a lower temperature as low as 100 °C. A detailed analysis revealed that Sm 3+ doping in CeO2 has increased the lattice volume, surface area, mesopore volume and engineered the surface defects. Higher concentrations of Ce 3+ and oxygen vacancies of Ce–Sm resulted in lowering of the band gap. It is evident from the H2 -TPR results that Sm 3+ doping in CeO2 strongly modified the reduction behavior of CeO2 by shifting the bulk reduction at a much lower temperature, indicating increased oxygen mobility in the sample which enables enhanced oxygen diffusion at lower temperatures, thus promoting reducibility, i.e., the process of Ce 4+ → Ce 3+ . UV-visible transmission studies revealed improved autocatalytic performance due to easier Ce 4+ /Ce 3+ recycling in the Sm 3+ doped CeO2 nanoparticles. From the in vitro cytotoxicity of both pure CeO2 and Sm 3+ doped CeO2 calcined at 500 °C in a concentration as high as 100 μg mL −1 (even after 120 h) on MG-63 cells, no obvious decrease in cell viability is observed, confirming their excellent biocompatibility. The presence of an increased amount of surface hydroxyl groups, mesoporosity, and surface defects have contributed towards an improved autocatalytic activity of mesoporous Ce–Sm, which appear to be a potential candidate for biomedical (antioxidant) applications.